Perencanaan Arsitektur Sistem Informasi pada Cafe Warung’e Dony Dengan Metode Zachman Framework - Afif, Muammar; AMBARWATI, AWALLUDIYAH; Setiawan, Eman (Universitas Komputer Indonesia, 2022)
Warung'e Dony is a business business in the culinary field that sells various variants of Indonesian coffee and food. This cafe operated in 2017 located in Sidoarjo which was founded by Dony Dewantara. The existing information system resources are not sufficient to handle existing business processes and cafe data has not been integrated, which results in frequent errors in the sales business process, for example, there is no system for integration of promotional activities, data collection of goods, and a manual cashier system. especially during this COVID-19 Pandemic, all transaction processes must be made completely digital to reduce the transmission of COVID-19. In planning and developing an integrated information system to support business needs and processes at Cafe Warung'e Dony, starting from data architecture, application architecture and technology architecture, the main activities include purchasing orders (PO), production processes and goods output. When building this application with architectural planning using the Zachman method, it can make it easier for buyers and employees to make transactions more secure in the conditions of the COVID-19 pandemic. Keywords— Zachman Framework. EAP